Combination of live and inactivated salmonella vaccines to protect against fowl typhoid in laying hens - Joaquim, Patricia Estefania; Balbiani, Facundo; Socas, Maria Laura; Morales, Hernando; Casey, Marcos; Rubio, Jesus; Chacana, Pablo (American Association of Avian Pathologists, 2025)
Fowl typhoid (FT) caused by Salmonella Gallinarum (SG) is a poultry disease distributed worldwide that has been eradicated in commercial production of many developed countries but still persists in many developing countries. Vaccination is one of the main strategies to reduce mortality, clinical signs, and vertical or horizontal transmission. The aim of this work was to assess the protection against FT conferred by vaccines based on Salmonella Enteritidis (SE), SG, or a combination. Five experimental groups of birds, vaccinated with different live or inactivated SG and SE vaccines were included in the trial: 1) two doses of a SG-SE bivalent inactivated vaccine; 2) four doses of the live attenuated SE vaccine; 3) three doses of the live attenuated SE vaccine and two doses of the SG-SE bivalent inactivated vaccine; 4) two doses of the live attenuated SG9R vaccine; and 5) unvaccinated birds. At 28 wk of age, all hens were challenged with a virulent strain of SG, and mortality was recorded during the subsequent 15 days. The results showed that the plan that included only the inactivated vaccine did not show significant protection (P = 1), while the plan based on the administration of the attenuated strain of SE significantly reduced mortality in the group of birds (P = 0.0309). However, the highest levels of protection were obtained in the group of hens immunized with the combination of the inactivated vaccine and the live attenuated SE strain (P < 0.0001), which was statistically similar to the homologous protection conferred by the SG 9R strain, a vaccine used in many countries to control FT. These results demonstrate that the combination of existing vaccines together with strict biosecurity measures on farms may help improve the control of the pathogen in countries where FT in an emerging or reemerging disease.